The handbook of historical economics - Bisin, Alberto; Federico, Giovanni, 1954- (Academic Press, an imprint of Elsevier, 2022)
The Handbook of Historical Economics guides students and researchers through a quantitative economic history that uses fully up-to-date econometric methods. The book's coverage of statistics applied to the social sciences makes it invaluable to a broad readership. As new sources and applications of data in every economic field are enabling economists to ask and answer new fundamental questions, this book presents an up-to-date reference on the topics at hand.